Determination of Environmental Exposure to DDT by Human Hair Analysis in Santos and São Vicente Estuary, São Paulo, Brazil - Carvalho, Daniele Fernandes Pena; Meire, Rodrigo Ornellas; Guimarães, Mariana Tavares; Pereira, Luiz Alberto Amador; Braga, Alfésio Luís Ferreira; Bernardo, Robson Roney; Torres, João Paulo Machado; Malm, Olaf (Orbital: The Electronic Journal of Chemistry, 2018)
In 2009, human hair samples were collected in Brazilian sites historically contaminated with organochlorine to assess the level of contamination with DDT and its metabolites in local human populations (Santos and São Vicente Estuary - São Paulo State). 122 hair samples from members of four contaminated community were collected (Pilões and Água Fria, Cubatão Center, Continental São Vicente and Guarujá), along with one non-contaminated sample (Bertioga). DDT and its metabolites were detected in approximately 70.0% of the hair samples from all areas, and its concentrations ranged from 50.3 ng.g-1 to 141.8 ng.g-1 in Cubatão Center and Pilões and Água Fria, respectively. The highest p,p’-DDT concentration was detected in Pilões and Água Fria (134 ng.g-1) and, Cubatão Center (43.9 ng.g-1) exhibited the lowest concentration. There was not a clear association between the occurrence of evaluated diseases and DDT detection in hair. None of the locally produced groceries appeared to be risk factors for the presence of DDT in hair. However, DDT concentrations found in this study showed an increase of DDT available for human exposure. These results strengthen the evidence of current exposure routes between DDT and the population of the estuarine region; therefore, this issue deserves further investigation. DOI: http://dx.doi.org/10.17807/orbital.v10i4.1089